Remittances, Export Performance, and Policy Frameworks in a Developing Economy: Countering the Dutch Disease Hypothesis in Nepal - Parajuli, Toya Narayan; Neupane, Prashanna (Journal of Innovation in Academia, 2025)
This study purpose to test whether larger remittance inflow supports or weakens Nepal’s export competitiveness. Annual data from 1994-2024 were used in this study, applying the export-centric ARDL bounds model with ECM and full diagnostics, modelling aggregate exports against remittance, GDP, import, and CPI. The data series are mixed I (0)/ I (1), cointegration is confirmed, and the error-correction term is found to be strong, indicating rapid adjustments. The result shows remittances have a positive but statistically insignificant effect on exports in the short and long run, providing macro-level insight into Dutch-Disease type crowding out. Export moves together with GDP and depend on imported intermediates. Remittance Granger causes imports but not exports. Stability, normality, and specification tests are stable. Thus, it concludes that Nepal’s challenge is not remittance-induced harm to tradables, but rather its failure to convert household savings into exportable capacity.